(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2019)
The goal of this contribution is to provide a brief overview of a theoretical introduction and terminology which are necessary for researching contact-induced language change. Namely, it was first neccessary to determine a wider theoretical framework by considering aspects of traductology, contact linguistics and sociolinguistics in translation research as well as language change in general, and then to determine a more narrow theoretical framework where we dealt with only translation as a site of contact and contact-induced language change.